Answer:
![\frac{2x^(2) }{{25} } + \frac{2y^(2)}{{25} } = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/tf3p92qyx9a6nil6mhxvt6la9b4v4gvz20.png)
Explanation:
Since the required hyperbola has its vertex at (5,0), its transverse axis is on the x-axis and center at (0,0).
So, we use the equation in standard form
![(x^(2) )/(a^(2) ) + (y^(2) )/(b^(2) ) = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/b41u16sly7ql9lb4u8p6yc1be0g2kc9dfh.png)
Also, since the path of the space probe gets closer to y = -x, this is the asymptote to the hyperbola.
Our standard asymptote equation is y = ±bx/a taking the negative sign and comparing with y = -x,
-bx/a = -x ⇒ b/a = 1 ⇒ a = b
Also, the coordinate of the vertex (c, 0) = (5, 0) and c² = a² + b²
substituting c = 5 and a = b into the equation, we have
c² = a² + b²
5² = a² + a²
25 = 2a²
a² = 25/2
a = √(25/2)
a = ±5/√2
rationalizing, we have
a = ±5/√2 × √2/√2
a = ±5√2/2
Since a = b, b = ±5√2/2
Inserting a and b into the equation for the hyperbola, we have
![(x^(2) )/(a^(2) ) + (y^(2) )/(b^(2) ) = 1\\(x^(2) )/(((5√(2) )/(2) )^(2) ) + (y^(2) )/((5√(2) )/(2) ^(2) ) = 1\\(x^(2) )/((25 X 2 )/(4) ) + (y^(2) )/((25X2 )/(4) ) = 1\\(x^(2) )/((25)/(2) ) + (y^(2) )/((25)/(2) ) = 1\\\frac{2x^(2) }{{25} } + \frac{2y^(2)}{{25} } = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/wzaldpszztzx3m2ysq9bqnhsam4lvwgxlg.png)
So, the required equation is
![\frac{2x^(2) }{{25} } + \frac{2y^(2)}{{25} } = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/tf3p92qyx9a6nil6mhxvt6la9b4v4gvz20.png)